2016
DOI: 10.1159/000452845
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study Examining the Effects of 8-Week Whey Protein versus Whey Protein Plus Creatine Supplementation on Body Composition and Performance Variables in Resistance-Trained Women

Abstract: Aims: We performed a pilot study examining the effects of whey protein and creatine supplementation (PRO + CRE group) versus whey protein supplementation (PRO group) alone on body composition and performance variables in a limited number of resistance-trained women. Methods: Seventeen resistance-trained women (21 ± 3 years, 64.7 ± 8.2 kg, 23.5 kg/m2, 26.6 ± 4.8% body fat, >6 months of training) performed a 4-day per week split-body resistance training program for 8 weeks. Subjects ingested either 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Tarnopolsky et al 8 found that 4-month creatine intake (0.10 g/kg/day) led to an increase in DXA-derived fat-free mass and reduction in bone breakdown among 31 children with DMD. Creatine also attenuated body fat accumulation in children with acute lymphoblastic leukemia during maintenance chemotherapy, 13 and adolescent combat athletes, 14 and increased whole-body lean body mass in cohorts that included adolescent vegetarians, 15 resistance-trained male and female teenagers, 16 - 18 and young soccer players. 19 Our findings back up a conclusion from above interventional trials about a tie-in linking creatine intake and body composition while extending this line of evidence to the populational level.…”
Section: Discussionmentioning
confidence: 94%
“…Tarnopolsky et al 8 found that 4-month creatine intake (0.10 g/kg/day) led to an increase in DXA-derived fat-free mass and reduction in bone breakdown among 31 children with DMD. Creatine also attenuated body fat accumulation in children with acute lymphoblastic leukemia during maintenance chemotherapy, 13 and adolescent combat athletes, 14 and increased whole-body lean body mass in cohorts that included adolescent vegetarians, 15 resistance-trained male and female teenagers, 16 - 18 and young soccer players. 19 Our findings back up a conclusion from above interventional trials about a tie-in linking creatine intake and body composition while extending this line of evidence to the populational level.…”
Section: Discussionmentioning
confidence: 94%
“…The qualified studies were mainly conducted in the USA [ 9 , 32 , 38 , 39 , 42 , 43 , 45–47 , 51–53 , 55–57 , 60–63 , 66–69 , 74 , 77 , 78 , 81 , 84 , 86 , 87 , 89 , 91 , 93 , 95 , 97 , 101 , 103 , 105 , 107–109 , 111 , 113 , 114 , 116–118 , 120 , 124 , 126 , 137 , 138 , 147 , 148 , 152 , 153 , 157 , 160 , 166 , 167 , 169 , 170 , 173 ], the UK [ 71 , 85 , 102 , 133 , 142 , 158 , 165 ], Sweden [ 35 ], Iran [ 112 , 121 , 143 ], Australia [ 41 , 44 , 70 , 76 , 98 , 99 ], France [ 36 , …”
Section: Resultsmentioning
confidence: 99%